A transmedia perspective on net.art narrative and its digimodernist context - Escobar Mengual, Blanca (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This article explores transmedia narratives and their digimodernist context through the literary-artistic phenomena that have emerged from Internet and a whole interconnected community on the net. Through a journey from the origins of net.art to its evolution towards NFTs and the Metaverse, it analyses the processes of digital writing and reading towards paid culture and intellectual property. Thus, it explores what the mission of literature is in these digital universes.